KARAKTERISTIK FASADE BANGUNAN PENINGGALAN KOLONIALISME DAN SEBARAN SPASIALNYA DI KOTA MAKASSAR - Pujantara, Ruly (FORUM BANGUNAN, 2013)
The Dutch Colonialism-Imperialism Buildings nowdays can be seen spread spatially at big towns in Indonesia., especially in Makassar, they were seen spread in the every corner of the town, because of Makassar or ujung pandang were one of the biggest port as a portal to east Indonesian region. The Dutch colonialism buildings has a certain form characteristic of Facade as European Architecture style, the originality of itâ€™s facades are changed as well, they are following the environment and climate in indonesia wich is a tropical climate, the changed characteristic and adaptation of facade characteristic itâ€™s will be a subject to discuss ini this journal.Â